Effect of ciprofol compared with propofol on hemodynamics in bronchoscope procedures during anesthetic induction: a randomized double-blind controlled study - Chen, Fang; Xing, Fang; Huang, Jiayu; Zhu, Junwen; Jiang, Ye; Li, Cheng (Frontiers in Medicine, 2025)
ObjectivePropofol poses hemodynamic challenges and injection pain during anesthesia. This study compared the effects of propofol and ciprofol, a novel propofol analog, on hemodynamics in painless bronchoscopy during induction of general anesthesia.MethodsA total of 250 patients underwent painless bronchoscopy anesthesia from October 2021 to June 2023. Randomly assigned to ciprofol or propofol groups, they received respective anesthesia. Changes in heart rate, blood pressure pre- and post-induction, after laryngeal mask airway placement, before and after fiberoptic scope insertion, incidence of choking and injection pain, vasoactive drug use, and satisfaction levels of operators, anesthesiologists, and patients were compared.ResultsCiprofol group showed significantly higher blood pressure 3 min post-induction compared to propofol group (80.81 ± 12.49 mmHg vs. 84.47 ± 12.80 mmHg, p = 0.023), with no significant difference post-bronchoscope placement. Injection pain incidence was significantly lower with ciprofol (0.8% vs. 37.1%, p < 0.001). Operators, anesthesiologists, and patients in ciprofol group reported higher satisfaction.ConclusionCiprofol exhibits less hemodynamic impact and injection pain than propofol, suggesting it as a viable alternative for anesthesia induction in bronchoscopy under general anesthesia with a laryngeal mask airway.Clinical trial registrationhttps://clinicaltrials.gov/, identifier [ChiCTR2200063048].